From Smart Camera to SmartHub: Embracing Cloud for Video Surveillance - Mukesh Kumar Saini; Pradeep K. Atrey; Abdulmotaleb El Saddik (International Journal of Distributed Sensor Networks)
Smart cameras were conceived to provide scalable solutions to automatic video analysis applications, such as surveillance and monitoring. Since then, many algorithms and system architectures have been proposed, which use smart cameras to distribute functionality and save bandwidth. Still, smart cameras are rarely used in commercial systems and real installations. In this paper, we investigate the reason behind the scarce commercial usage of smart cameras. We found that, in order to achieve scalability, smart cameras put additional constraints on the quality of input data to the vision algorithms, making it an unfavourable choice for future multicamera systems. We recognized that these constraints can be relaxed by following a cloud based hub architecture and propose a cloud entity, SmartHub, which provides a scalable solution with reduced constraints on the quality. A framework is proposed for designing SmartHub system for a given camera placement. Experiments show the efficacy of SmartHub based systems in multicamera scenarios.